Dampak Degradasi Lingkungan Terhadap Potensi Pengembangan Ekowisata Berkelanjutan di Delta Mahakam: Suatu Tinjauan - Dana Adikusuma; Emmy Yuniarti Rusadi; Nurvina Hayuni (Jurnal Wilayah dan Lingkungan, 2014)
The aim of this research is formulating the general concepts for ecotourism development based on its environmental degradation on Mahakam Delta. The research method is descriptive-analytic with critically and comprehensively review on several researches done. Those are not only from scientific and technology dimension, but also policy on strategic issues-based regional development. The result of this research is conclude that environmental degradation phenomena in Mahakam Delta was located on critical very high level. It is almoust 80 % of 1000 Km2 of this area. The main factors are consist of land conversion and mining and gas exploitation. The integrated and environmental-friendly solution are required to solve the problems, such as eco-tourism development program. The program was focused on three fundamental principle. Those are consist of conservation values, community involvement and sustainable. It has several inovative concepts to make eco-tourism development success. It also has several indicators for each concepts to explain them. The concepts are consist of policy development, biogeophisical management and sustainable eco-tourism development.